Epidemiology and antimicrobial resistance of Mycobacterium spp. in the United Arab Emirates: a retrospective analysis of 12 years of national antimicrobial resistance surveillance data - Thomsen, Jens; Abdulrazzaq, Najiba M.; Nyasulu, Peter S.; Al Hosani, Farida; Habous, Maya; Weber, Stefan; Jabeen, Fouzia; , The UAE AMR Surveillance Consortium; Menezes, Godfred Antony; Moubareck, Carole Ayoub; Senok, Abiola; Everett, Dean B.; et al. (Frontiers in Public Health, 2024)
The Eastern Mediterranean Regional Office (EMRO) region accounts for almost 8% of all global Mycobacterium tuberculosis (TB) cases, with TB incidence rates ranging from 1 per 100,000 per year in the United Arab Emirates (UAE) to 204 per 100,000 in Djibouti. The national surveillance data from the EMRO/ Middle East and North Africa (MENA) region on the epidemiology and antimicrobial resistance trends of TB, including MDR-TB remains scarce.A retrospective twelve-year analysis of N=8,086 non-duplicate diagnostic Mycobacterium tuberculosis complex (MTB complex) isolates from the UAE was conducted. Data were generated through routine patient care during the 2010-2021 years, collected by trained personnel and reported by participating surveillance sites to the UAE National Antimicrobial Resistance (AMR) Surveillance program. Data analysis was conducted with WHONET, a windows-based microbiology database software developed by the World